Ultra-fast intramolecular singlet fission to persistent multiexcitons by molecular design - Pun, Andrew B.; Asadpoordarvish, Amir; Kumarasamy, Elango; Tayebjee, Murad J. Y.; Niesner, Daniel; Mccamey, Dane R.; Sanders, Samuel N.; Campos, Luis M.; Sfeir, Matthew Y. (Nature Chemistry, 2019)
Singlet fission-that is, the generation of two triplets from a lone singlet state-has recently resurfaced as a promising process for the generation of multiexcitons in organic systems. Although advances in this area have led to the discovery of modular classes of chromophores, controlling the fate of the multiexciton states has been a major challenge; for example, promoting fast multiexciton generation while maintaining long triplet lifetimes. Unravelling the dynamical evolution of the spin- and energy conversion processes from the transition of singlet excitons to correlated triplet pairs and individual triplet excitons is necessary to design materials that are optimized for translational technologies. Here, we engineer molecules featuring a discrete energy gradient that promotes the migration of strongly coupled triplet pairs to a spatially separated, weakly coupled state that readily dissociates into free triplets. This 'energy cleft' concept allows us to combine the amplification and migration processes within a single molecule, with rapid dissociation of tightly bound triplet pairs into individual triplets that exhibit lifetimes of similar to 20 mu s.